High salt intake and bone health in postmenopausal women: exposing the lack of studies – a systematic review and meta-analysis - Imash, Dinara; Gusmanov, Arnur; Chan, Mei-Yen (Frontiers in Endocrinology, 2025)
IntroductionOsteoporosis is a common health concern among women after menopause, partially due to declining estrogen levels, which are a major regulator of bone metabolism and calcium retention. This work presents the first systematic synthesis of evidence assessing the impact of dietary sodium intake on bone health among postmenopausal women. Although there is substantial research demonstrating that reducing sodium intake can lower urinary calcium excretion, much of this evidence has been derived from studies conducted in mixed populations, often without stratifying by age, sex, or hormonal status. Postmenopausal women, who are at increased risk for bone loss and calcium imbalance due to hormonal changes, remain significantly underrepresented in this body of literature. This research examines the impact of dietary salt on maintaining bone tissue structure and relates it to calcium excretion through urine as a marker of bone demineralization.MethodsA systematic review and meta-analysis were conducted in accordance with the guidelines for reporting systematic reviews. Systematic searching of four major databases, i.e., PubMed, EMBASE, Web of Science, and the Cochrane Library, was done to find reports of randomized controlled trials estimating the influence of sodium intake on calcium excretion in urine and on bone health indicators. Meta-analysis was used to synthesize evidence to estimate the effect of sodium intake on calcium excretion.ResultsSix articles out of an initial 596 made it into the stringent selection criteria. The meta-analysis revealed that high sodium diets significantly increased urinary excretion of calcium in women after menopause, with a pooled mean difference of 29.38 mg/day (95% CI: 12.31 to 46.46, p < 0.01). These findings highlight the detrimental impact of excessive salt consumption on bone health, demonstrating a link between sodium consumption and accelerated loss of bone mass. Conclusion: Based on the findings of the review, limiting dietary sodium consumption is recommended as a way to help prevent osteoporosis in postmenopausal women.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025643910, identifier CRD42025643910.